An LP/CBP reconfigurable analog baseband circuit for software-defined radio receivers in 65 nm CMOS. Issue 1 (January 2015) - Zhang, Xinwang; Liu, Bingqiao; Wang, Zhihua; Chi, Baoyong
Abstract A low pass (LP) and complex band pass (CBP) reconfigurable analog baseband circuit for software-defined radio (SDR) receivers is presented. It achieves 1–15 MHz LP bandwidth, 2–8 MHz CBP bandwidth and 0–36 dB gain range with 1 dB step. Nulling-resistor Miller feed-forward (NRMFF) differential-mode compensation, passive left half-plane (LHP) zero common-mode compensation and Quasi-Floating Gate (QFG) technique are proposed to improve the high frequency performance and driving capability of the embedded fully differential operational amplifier (Op-Amp). The analog baseband circuit has been implemented in 65 nm CMOS. It achieves 15.2 dB m/27.1 dB m IB/OB-IIP3, −2 dB m IP1dB and 71 dB m IIP2 while consuming 3.6–9.1 mW from a 1.2 V power supply and 0.75 mm2 chip area.